Structural properties of lotus seed starch prepared by octenyl succinic anhydride esterification assisted by high hydrostatic pressure treatment. (January 2020) - Sun, Siwei; Lin, Xiong; Zhao, Beibei; Wang, Bailong; Guo, Zebin
Abstract: This paper describes a new method for combining high hydrostatic pressure (HHP) and octenyl succinic anhydride (OSA) esterification for starch modification. The degree of substitution (DS) was 0.0148–0.0389 when the OSA concentration increased from 3% to 9%, whereas after HHP treatment, the DS decreased, especially for H-OSA-9%, from 0.0389 to 0.0125. Scanning electron microscopy indicated that OSA with combined HHP treatment destroyed the surface morphology of the starch. FTIR spectroscopy revealed two new absorption peaks at 1526 cm −1 and 1728 cm- 1 . The particle size of OSA-LS and H-OSA-LS increased significantly (P < 0.05), except H-OSA-9%, owing to the hydrophobic groups introduced into the starch during the esterification reactions; consequently, the starch powders tended to swell and aggregate in aqueous solution. The Mw, Mn, and Mw / Mn of amylose decreased slightly with OSA treatment. The X-ray diffraction patterns confirmed that the crystalline patterns of OSA-LS and H-OSA-LS were preserved, but the crystallinity decreased to different degrees. These results indicated that H-OSA-LS provided conditions for encapsulating lipophilic substances, thus providing a potential direction for further research. Highlights: HHP combined OSA is a innovative method for starch modification. The surface morphology and particle size of H-OSA-LS are different from OSA-LS. OSA-LS released more amylose which is favorable for the formation of lipid complexes.